THE LEGAL ORDER OF THE EUROPEAN UNION AND CONSEQUENCES IN THE IMPLEMENTATION OF THE EUROPEAN NORMS IN THE NATIONAL LAW OF THE MEMBER STATES - CHIRTOACA, Natalia (Ecoforum Journal, 2022)
This article analyses the specifics of the legal order of the European Union, which creates a complex and original system of law, being more of a supranational law than an international law. In other words, original Community law is international in creation and supranational in application.The research highlights the most important features of the legal order of the European Union, in the sense that EU law is immediately applicable, has direct applicability and is applied with priority over any national rule. At the same time, we believe that the characteristic features of the legal order of the European Union have their origin in the partial ceding of some attributes of sovereignty to atypical supranational bodies, to which the Member States resorted when they established the European Union.Finally, we specify that European legislation creates a specific legal order that integrates into the national legal order. From this integration arises the impossibility of prevailing a subsequent national norm contrary to European law. Any other solution would deprive European law of its uniform application, as it would vary according to the subsequent national law of each Member State. A differentiated application by each Member State would lead to discrimination based on nationality / citizenship, discrimination which is prohibited by express provisions of European law